Fabricação de tijolo solo-cimento com incorporação de lodo de ETA - Gontijo Neto, Trajano Machado (Universidade Federal do Tocantins, 2023)
The present study contemplates the process of analysis and development of a masonry block of soil cement with the incorporation of inorganic residues in its composition. This study was carried out by replacing part of the soil with a mass of inorganic residues. Two different, comparative tests were carried out, using sludge proportions in two periods: rainy and estimation. The inorganic components are from the sludge from the Water Treatment Stations (ETA) in the municipality of Palmas/TO and which currently do not have their own dump, being stored in large bags inside the concessionaires' own yards. From a methodology focused on a complete factorial at two different levels with two independent variables: proportion of water sludge planning (%) and proportion of cement (%), the mechanical strength and absorption of blocks were evaluated. of soil-cement through the surfaces of optimized responses, where the mechanical behavior and water absorption in different functions can be visualized. With the results of blocks of 3, it was possible to establish a ETA of % by mass that suffered a replacement of 3 soil by masonry residues. In this degree of waste replacement, only 16% of cement was used, with a mechanical strength of 2.10 (± 0.26) Mpa and a water absorption of 15%. 10 that meet as possible to produce, 9484 cells possible to produce a block/9484, using the largest amount of waste and the least amount of blocks. Thus, the product presented was developed with an innovative and sustainable material, and can be used as a sealing material in civil construction.